Thermal recovery of organic solid waste by aerobic process: fuel derived from food waste - PEREIRA DE SÁ, FERNANDO; CARDOSO DE LIMA BORGES, ELISANGELA (Latin American Journal of Energy Research, 2025)
The inadequate disposal of food waste represents an environmental and energy challenge. Pressurized aerobic digestion emerges as an innovative alternative, enabling the reduction of residual mass and the production of biocompost with energy characteristics. In this study, food waste was subjected to controlled aerobic digestion for 14 days, resulting in mass reductions ranging from 60% to 79%. The obtained biocompost was characterized in terms of its physicochemical composition, with carbon content ranging from 37% to 44% and low sulfur content (
Keywords: aerobic biodigestion; food waste; calorific value; solid biofuel.